Addition of Etravirine Does Not Enhance the Initial Decline of HIV-1 RNA in Treatment-Experienced Patients Receiving Raltegravir. (1st August 2017) - Flandre, Philippe; Marcelin, Anne-Geneviève; Calvez, Vincent
Abstract : Objective: The importance of an early reduction of HIV-1 RNA as a marker for positive longer term outcome is still under debate. We investigate whether antiretroviral-experienced patients receiving raltegravir plus etravirine have a higher early reduction of HIV-1 RNA compared with patients receiving raltegravir. Design: An observational study of treatment-experienced patients. Methods: The objective is to investigate 349 patients included in a raltegravir resistance study. The early outcome is defined as a reduction of HIV-1 RNA at week 8. The crude method defines all measurements below the limit of quantification to be equal to the limit of quantification provides biased estimates. Such a reduction is censored by the limit of quantification and is subject to selection bias in observational studies. Results: The crude method showed a significant higher reduction in HIV-1 RNA reduction in patients receiving raltegravir plus etravirine compared with patients receiving raltegravir (mean reduction of 2.1 versus 1.8 log10 copies/mL). However, survival methods adjusted for both censoring, due to the limit of quantification, and confounding factors lead to a nonsignificant difference between the 2 treatment groups (mean reduction of 2.8 versus 2.7 log10 copies/mL). Conclusion: Taking into account censoring and confounding factors, our study did not demonstrate a higher early reduction of HIV-1 RNA in patients receiving raltegravir with versus without etravirine.